2020
DOI: 10.1155/2020/2313504
|View full text |Cite
|
Sign up to set email alerts
|

Extended Spectrum β-Lactamase-Mediated Resistance and Antibiogram of Pseudomonas aeruginosa Isolates from Patients Attending Two Public Hospitals in Khartoum, Sudan

Abstract: Treating infections caused by Pseudomonas aeruginosa is challenging. In addition to its intrinsic ability to develop resistance to multiple classes of antibiotics, it also produces extended-spectrum β-lactamase (ESBL). Continuous update of the antibiograms is required to cope with the rate of the emergence of antibiotic resistance. This study aimed to determine the antimicrobial susceptibility pattern and to determine the frequency of ESBL production among the P. aeruginosa isolates from patients at two public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
0
1
Order By: Relevance
“…The bacteria P. aeruginosa were 100% resistant to 9 different drugs and 100% susceptible to colistin and medium – low resistance rate was noted to piperacillin/tazobactam (65%) and aztreonam (35%). In contrast to our study, the studies from Sudan [53] and Egypt [54] observed that the bacteria had low resistance rate and high susceptible to the above-mentioned drugs. In the case of A. baumannii , the bacteria were 100% resistant to 11 drugs which are given in the table 4, higher resistance rate (70% - 80%) was observed on the ampicillin/sulbactam & trimethoprim/sulfamethoxazole and 30% resistance to colistin.…”
Section: Discussioncontrasting
confidence: 99%
“…The bacteria P. aeruginosa were 100% resistant to 9 different drugs and 100% susceptible to colistin and medium – low resistance rate was noted to piperacillin/tazobactam (65%) and aztreonam (35%). In contrast to our study, the studies from Sudan [53] and Egypt [54] observed that the bacteria had low resistance rate and high susceptible to the above-mentioned drugs. In the case of A. baumannii , the bacteria were 100% resistant to 11 drugs which are given in the table 4, higher resistance rate (70% - 80%) was observed on the ampicillin/sulbactam & trimethoprim/sulfamethoxazole and 30% resistance to colistin.…”
Section: Discussioncontrasting
confidence: 99%
“…These bacteria also produce plasmid-mediated enzymes that hydrolyze the oxyimino β lactams and the monobactams called expanded spectrum beta-lactamases (ESBLs). ESBLs confer a powerful resistance against ß-lactam antibiotics and third-generation cephalosporins such as ceftazidime, ceftriaxone, and cefotaxime inactive (19).…”
Section: Introductionmentioning
confidence: 99%